2022
DOI: 10.1101/2022.04.01.486695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron breakthrough infection drives cross-variant neutralization and memory B cell formation

Abstract: Omicron is the evolutionarily most distinct SARS-CoV-2 variant (VOC) to date and displays multiple amino acid alterations located in neutralizing antibody sites of the spike (S) protein. We report here that Omicron breakthrough infection in BNT162b2 vaccinated individuals results in strong neutralizing activity not only against Omicron, but also broadly against previous SARS-CoV-2 VOCs and against SARS-CoV-1. We found that Omicron breakthrough infection mediates a robust B cell recall response, and primarily e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Moreover, several studies reported stem-directed antibody- mediated protection against H5N1 and H7N9 zoonotic influenza strains through hemagglutinin imprinting during childhood resulting from exposure to seasonal H1N1 and H3N2, respectively ( 48, 50 ). Similarly, we show that exposure to the antigenically shifted Omicron primarily leads to a recall of existing memory B cells specific for epitopes shared by multiple SARS-CoV-2 variants rather than by priming naïve B cells recognizing Omicron-specific epitopes (at least up to 100 days post breakthrough infection), as also recently reported ( 51 ). Although immune imprinting may be beneficial in stimulating responses to cross-reactive SARS-CoV-2 epitopes, antibody responses to some Omicron-specific epitopes were markedly diminished by prior antigenic exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, several studies reported stem-directed antibody- mediated protection against H5N1 and H7N9 zoonotic influenza strains through hemagglutinin imprinting during childhood resulting from exposure to seasonal H1N1 and H3N2, respectively ( 48, 50 ). Similarly, we show that exposure to the antigenically shifted Omicron primarily leads to a recall of existing memory B cells specific for epitopes shared by multiple SARS-CoV-2 variants rather than by priming naïve B cells recognizing Omicron-specific epitopes (at least up to 100 days post breakthrough infection), as also recently reported ( 51 ). Although immune imprinting may be beneficial in stimulating responses to cross-reactive SARS-CoV-2 epitopes, antibody responses to some Omicron-specific epitopes were markedly diminished by prior antigenic exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, it is worth noting that Omicron breakthrough infection mediates a robust B-cell recall response, expanding preformed memory B cells that recognize the epitopes shared by different variants [ 23 , 24 ]. It has been reported that the preformed B-cell memory pool has sufficient plasticity to be remodeled by exposure to heterologous S protein, allowing the effective neutralization of other variants [ 25 ]. Therefore, we consider that breakthrough infection with Omicron could enrich the memory B-cell plateaus of vaccinated individuals and recall preexisting B cells, which recognize the conserved S protein epitopes and provide cross-protection.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, hybrid immunity resulting from infection-acquired immunity boosted with vaccination conferred the strongest, or longer-lasting protection, respectively [33, 34]. Similarly, Omicron break-through infections in previously vaccinated individuals have been shown to drive cross-variant neutralization and memory B cell formation [35], suggesting that a combination of both, natural infection and vaccination, will have more impact on the future COVID-19 epidemiology than one of the events alone.…”
Section: Conclusion and Discussionmentioning
confidence: 99%